Stealing home : looting, restitution, and reconstructing Jewish lives in France, 1942-1947 - Fogg, Shannon Lee (Oxford University Press, 2017)
A social history focusing on the individual stories of Jewish Holocaust survivors in France as they tried to rebuild their lives after the war: examining the looting of private apartments in Paris as part of the German occupiers' plunder of France, and analysing Jewish attempts to reclaim their possessions in the war's immediate aftermath.